A socioeconomic analysis of GO-NGO versus self-managed dairy farming in two districts of Bangladesh (Bangladesh Journal of Animal Science, 2014)
With a view to address the present status of intervention received by dairy farmers from different government and non-government organizations and its impact on farmers livelihood pattern in relation to self-managed farmers, this present study was performed in two districts of Bangladesh namely, Manikganj and Sirajganj. Altogether 165 dairy farmers were selected from two districts. A combination of descriptive, statistical and mathematical techniques was applied to achieve the objectives and to get the meaningful results. The BCR were 2.3 for NGO supported and 2.4 for GO supported farmers. The productivity in terms of physical volume was higher in case of supported dairy farmers for both the areas which were tested by t-statistics. In determining the effects of the different variable inputs, four out of six variables (i.e., labor cost, paddy straw cost, green grass cost and concentrate feed cost) were found to have significant effect on gross returns from milk production for both supported and self-managed farmers. To accomplish the profit maximization, all types of dairy farmers have scope to attain full efficiency in milk production by reallocating the resources. Supported farm created greater opportunity for employment of both male and female than self-managed dairy farmers. Ravallion test results showed that the income was increased by the amount of Tk. 25400.6 due to intervention. Expenditure elasticity was also estimated at 0.40% which means that expenditure increased by 0.40%, on an average, due to 1% increase in income, other things remaining the same. The asset pentagon approach shows that there is a noteworthy improvement based on different capitals namely, human capital, social capital, natural capital, physical capital and financial capital of supported dairy farming. Although dairy farmers reported problems of low price of output, inadequate capital, etc., these could be minimized if both government and non-government organizations take proper measures in this regard, which will ultimately lead to improve farmers socioeconomic conditions and livelihood status.DOI: http://dx.doi.org/10.3329/bjas.v43i3.21656 Bang. J. Anim. Sci. 2014. 43 (3): 232-241